"I want to do well for myself as well!": Constructing coaching careers in elite women`s football - Ronkainen, N. J.; Sleeman, E.; Richardson, D. (Sports Coaching Review, 2020)
There is a limited understanding of the career development of sport coaches and how they design their lives in and through sport. We drew on career construction theory and narrative methodology to explore football coaches` career development, adaptability resources, and the meanings they assigned to their journeys. Ten women`s football (soccer) coaches (2 women) aged 23-60 in England took part in narrative interviews. Our analysis indicated that early immersion into the football narrative context often resulted in low career exploration and a strong commitment to coaching as an attempt to keep the footballing identity narrative "going". The coaches were resourceful in crafting their coaching careers; however, most of them expressed little concern or curiosity for other careers, leaving them vulnerable to psychological distress if unable to realise their career ambition. Women`s elite football presented a novel, attractive context for quicker career advancement and developing an elite coach identity.